Performance and lifetime of micro-channel plate tubes for the TORCH detector - Gys, T; García, L; Fopma, J; Forty, R; Frei, C; Gao, R; Harnew, N; Keri, T; Piedigrossi, D (Elsevier, 2014)
Timing Of internally Reflected CHerenkov photons (TORCH) is a time-of-flight detector proposed for particle identification at low momentum. Charged particles passing through a plane of quartz produce Cherenkov light, some of which is trapped within the plane by total internal reflection and then emerges at the edges. There the photons are focused onto micro-channel plate photon detectors that register their position and arrival time. This allows reconstructing the photon trajectories in quartz and determining the particle crossing time. Commercial micro-channel plate tubes can achieve the required timing resolution, but their anode spatial segmentation is too coarse, at least in one dimension. In addition, these devices must survive a number of years in a high occupancy environment. Micro-channel plate tubes specifically dedicated to the TORCH are currently being designed, constructed and prototyped in collaboration with industry. In the present paper, results from commercial and dedicated devices are reported.